Pierwsza ekranizacja Pana Twardowskiego - Małgorzata Hendrykowska; Marek Hendrykowski (Images)
The article discusses the oldest recorded film adaptation of the legend of Pan Twardowski, found in the archives of the George Eastman House in Rochester, New York. The two-part feature film was filmed in Russia between 1916 and 1917, and its creator was the famed Polish filmmaker Władysław Starewicz.